Explaining differences in self-focused and other-involved public health preventive behaviors between the US and China: the role of self- construal and health locus of control - Pan, Wenjing; Liao, Wang; Feng, Bo; Li, Siyue (Frontiers in Public Health, 2024)
This study examined national similarities and differences in people's engagement in health preventive behaviors during a public health crisis. Two cross-sectional surveys were conducted in the United States (N = 888) and China (N = 844). A conceptual distinction was made between selffocused and other-involved preventive behaviors in response to public health crises. The results showed that American participants reported greater engagement in self-focused preventive behaviors than Chinese, whereas Chinese participants reported greater engagement in other-involved preventive behaviors than Americans. Chinese participants also engaged more in other-involved than selffocused preventive behaviors. Self-construal and health locus of control partially explained the observed differences in engagement in preventive behaviors. Implications were discussed regarding health communication research.